Ð ÐµÐ°ÐºÑ†Ð¸Ñ Ð¿Ð°Ñ€ÐµÐ½Ñ…Ð¸Ð¼Ñ‹ Ð¿ÐµÑ‡ÐµÐ½Ð¸ Ð½Ð° Ð¿Ð¾Ð´ÐºÐ¾Ð¶Ð½Ð¾Ðµ Ð²Ð²ÐµÐ´ÐµÐ½Ð¸Ðµ Ñ„Ñ€Ð°Ð³Ð¼ÐµÐ½Ñ‚Ð¾Ð² Ñ‚ÐºÐ°Ð½ÐµÐ¹ Ñ‰Ð¸Ñ‚Ð¾Ð²Ð¸Ð´Ð½Ð¾Ð¹ Ð¶ÐµÐ»ÐµÐ·Ñ‹ Ð¸ Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ‹ Ð¿Ñ€Ð¸ ÑÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ð¾Ð¼ Ð³Ð¸Ð¿Ð¾Ñ‚Ð¸Ñ€ÐµÐ¾Ð·Ðµ - Chuykova, V. I.; Yurchenko, T. N.; Sharlay, T. M.; Strona, V. I.; Zhulikova, E. P.; Marchenko, L. N.; Govorukha, T. P.; Repin, N. V.; Kovalev, A. S.; Kondakov, I. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2011)
There were investigated the morphological and morphometric characteristics of rat liver parenchyma during hypothyroidism and after its correction by subcutaneous introduction of the fragments of cryopreserved xenogenic fetal thyroid gland (CXFTG), fragments of cryopreserved allogenic placenta (CAP) and their combined introduction. The modelling of medicamental hypothyroidism has been shown to be accompanied by evident liver parenchyma proteinosis. Introduction of CXFTG stimulates intracellular hepatocyte proliferation revealed in the increased binuclear hepatocyte number to the 14th day. At the same time during combined introduction of CXFTG and CAP this effect has been already observed to the 7th day after introduction.